Maturation of Marriage Age According to Bkkbn in Juridical, Psychological, and Economic Perspectives - ., Teresa; ., Zuhraini; Qodir Zaelani, Abdul; Tahmid, Khairuddin (KnE Social Sciences, 2024)
Law No. 1 of 1974 article 7 paragraph 1 regarding the age limit of marriage is considered no longer relevant to the present; therefore, the government stipulates the latest regulation of Law No. 16 of 2019 regarding the age limit of marriage. There are various perspectives on the age limit of marriage from the perspectives of Islamic law, law, and BKKBN. The problem that arises is the updated law not being able to provide the best solution regarding the minimum age limit for marriage in Indonesia, due to various aspects ranging from juridical, psychological, and economic aspects, considered not ready to live a married life. This study aims to describe the recommended age limit for marriage for both men and women, and also describes the reasons after being seen from juridical, psychological, and economic aspects. This research uses library research, while the research method used is descriptive analysis, which is to analyze the impact of getting married at an age that is still in the teens or the latest law for men and women of 19 years from a juridical, psychological, and economic perspective. From this explanation, it can be concluded that women aged 21 years and men aged 25 years are considered to be juridically capable, able to regulate emotions psychologically, have a more stable economy, and a more decent job. Keywords: maturation of marriage age, ideal age